'Pictures from Beyond the Eastern Border': Socialist Television in Finland, 1963 to 1988 - Mari Pajala (Sage Publications, Inc., 2022)
Recent research has criticized a tradition of seeing socialist media cultures as strictly separated from the West. While scholars have analyzed how socialist television institutions reacted to influences from Western media, there is little research on how socialist television culture traveled outside the socialist bloc. This article analyses the ways in which state socialist television culture appeared in Finland on the basis of the main Finnish TV guide magazine Katso in 1963, 1968, 1973, 1978, 1983, and 1988. The article argues that socialist television was a significant influence in the Finnish television environment. Finnish audiences were introduced to socialist television cultures through means such as cross-border access to Soviet broadcasts and journalistic depictions. Both public service and commercial television companies imported Eastern European programs of various genres. Thus, the Finnish case shows that a strict East/West binary is not helpful for understanding European television history.